2013
DOI: 10.1177/0269215512469120
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of a mixed Kinesio taping–compression technique on venous symptoms, pain, peripheral venous flow, clinical severity and overall health status in postmenopausal women with chronic venous insufficiency

Abstract: Mixed Kinesio taping-compression therapy improves symptoms, peripheral venous flow and severity and slightly increases overall health status in females with mild chronic venous insufficiency. Kinesio taping may have a placebo effect on pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
2
16

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 34 publications
(52 reference statements)
2
34
2
16
Order By: Relevance
“…Aguilar--Ferrándiz, vaka grubumuza benzer şekilde KVY tanılı hastalarla çalışmayı ter--cih etmiştir (1,4). Hafif--orta düzey KVY tanılı postmenopozal kadınlara dört hafta boyunca gerçek KT uygulaması yaptığı grubun venöz semptomlarında ve ağrısında azalma, venöz geri dolum zamanında ve venöz pompa fonksiyonunda artma sap--tamıştır.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Aguilar--Ferrándiz, vaka grubumuza benzer şekilde KVY tanılı hastalarla çalışmayı ter--cih etmiştir (1,4). Hafif--orta düzey KVY tanılı postmenopozal kadınlara dört hafta boyunca gerçek KT uygulaması yaptığı grubun venöz semptomlarında ve ağrısında azalma, venöz geri dolum zamanında ve venöz pompa fonksiyonunda artma sap--tamıştır.…”
Section: Discussionunclassified
“…Ancak, kompresyon çoraplarının veya sert bandajların cilt irritasyonu, ağrı, anestezik etki gibi konforsuzluklar oluşturması kul--lanımlarını güçleştirir. Bu durum, klinis--yenleri alternatif yöntemleri kullanmaya ve güncel bantların KVY tedavisindeki et--kinliğini araştırmaya sevk etmiştir (4).…”
unclassified
“…Chou et al 15 have suggested that KT methods could be an alternative for the classical lymphedema therapies for the patients with lymphedema occured secondary to breast cancer. Aguilar-Ferrándiz et al 16 have applied an KT for mild chronic venous insufficiency. They stated that mixed KT-compression therapy produces a slight improvement in overall health status and may have a placebo effect on venous pain.…”
Section: Discussionmentioning
confidence: 99%
“…Vários estudos tem mostrado que a aplicação da Kinesio Taping reduz a dor, mas seu mecanismo de ação permanece desconhecido 18-22 . Acredita-se que o estímulo cutâneo promovido pela faixa causa um feedback proprioceptivo cutâneo, reduzindo a dor 21,22 . Todavia, autores sugerem que a aplicação da Kinesio Taping placebo é capaz de reduzir os níveis de dor, provavelmente pelo estímulo visual (cores) que geram expectativas positivas nos resultados de dor 23 .…”
Section: Discussionunclassified